Developing and Validating the Refugee Integration Scale in Nairobi, Kenya. (24th July 2016) - Beversluis, David; Schoeller-Diaz, David; Anderson, Martin; Anderson, Natalie; Slaughter, Amy; Patel, Ronak B.
Abstract : The humanitarian trend of protracted refugee situations and urban displacement are driving de facto integration of urban refugees in host countries. Facilitating this process through local programmes and policies is an important long-term solution for urban refugees that can no longer be ignored. Tools to measure refugee integration are required to conduct research and to guide programmes and policy. This study describes the development and validation of a 25-item Refugee Integration Scale (RIS) using standard scale development methodology among Somali and Banyamulenge refugees in Nairobi, Kenya. We report mixed-methodology methods to strengthen the scale's validity and reliability. These include a literature review and a qualitative focus group component among refugees in Nairobi to establish a theoretical construct for urban refugee integration. The scale was then piloted and refined through a quasi-randomized survey of 331 refugees in Nairobi. Reliability was established as Cronbach's alpha 0.861 indicating high internal consistency. The RIS is a continuing step towards better understanding and measuring urban refugee integration, and will help to guide policies and programmes for this vulnerable population.